2014
DOI: 10.1007/s10804-014-9196-8
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and Relatedness in Adolescence and Emerging Adulthood: Relationships with Parental Support and Psychological Distress

Abstract: Autonomy and relatedness are fundamental needs both in adolescence and in emerging adulthood which are affected by parental support and are linked to children's psychological distress. The study investigated autonomy and relatedness in late adolescents and emerging adults living in Italy, analyzing the relationships with perceived parental support and psychological distress. Selfreport data were collected from a sample of 325 Caucasian adolescents and emerging adults (males = 41 %) ranging in age from 17 to 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
166
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 79 publications
15
166
0
9
Order By: Relevance
“…Although individuals increasingly display autonomous functioning from their parents during this period, parents continue to play a significant role (Arnett 2004;Inguglia et al 2015;Soenens and Beyers 2012;. As a result, the most studied parenting dimensions are psychological control and autonomy-supportive parenting (Fousiani et al 2014;Soenens and Beyers 2012;Soenens et al 2009), both of which have been found to be associated with internalizing problems in emerging adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although individuals increasingly display autonomous functioning from their parents during this period, parents continue to play a significant role (Arnett 2004;Inguglia et al 2015;Soenens and Beyers 2012;. As a result, the most studied parenting dimensions are psychological control and autonomy-supportive parenting (Fousiani et al 2014;Soenens and Beyers 2012;Soenens et al 2009), both of which have been found to be associated with internalizing problems in emerging adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy is defined as the sense of volition, the desire to self-organize experience and behavior, and to have activity concordant with one's integrated sense of self. Relatedness is defined as the feeling of being connected to others, of loving, caring, and being loved and cared for, and establishing high quality, satisfying and positive bonds with others (Deci and Ryan 2000;Inguglia et al 2015). Finally, competence is considered as the experience of a sense of effectiveness in interacting with one's environment (White 1959).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that parents still play a key role in the development of students' psychological autonomy during emerging adulthood. Students whose parents provided a unique combination of high care and low control had better adjustment across several domains of college-related issues (Inguglia, Ingoglia, Liga, Lo Coco, & Lo Cricchio, 2015;Smojver-Ažić, Martinac Dorčić, & Juretić, 2015). Students who do not develop emotional independence and still need approval from their parents feel more pressure to fulfil parental expectations, which undermine their learning capacities, resulting in lower academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this inference is that a significant body of research across various domains suggests that improved parent relatedness fosters children's development of desirable psychosocial and performance characteristics. For example, as reported in Chapter 2, parental relatedness support has been positively associated with children's well-being (e.g., Milyavskaya et al, 2009;Veronneau et al, 2005); and negatively associated with child characteristics associated with poor well-being (e.g., King, 2015;Inguglia et al, 2014). I also previously outlined the link between parental ability to support children's relatedness BPN and factors relating to children's performance in Chapter 2 (and I summarize these outcomes again in Part B of this study).…”
Section: Discussionmentioning
confidence: 90%